Double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance as well as preparation method and application of double-layer composite microcapsule
By adopting a double-layer composite microcapsule structure, combined with phase change materials and self-repair materials, the problems of microcapsule phase change materials in the prior art are easily leaked, single source of heat energy, and monotonous functions, achieving efficient anti-icing and self-repairing effects in low-temperature environments.
Patent Information
- Application Number
- CN202411947948.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing microcapsule phase change materials have problems such as easy leakage, single source of heat energy, and monotonous functions, making it difficult to maintain anti-icing and de-icing performance under dark or cloudy conditions.
A double-layer composite microcapsule structure is adopted, in which the inner layer is a phase-change microcapsule core composed of n-octanoic acid, tetradecane and sodium polyacrylate emulsifier, and a phase-change microcapsule shell composed of carbon nanotubes and bipolymers. The outer layer is a self-healing microcapsule core and shell composed of hydrophobic hexamethylene diisocyanate, carbon nanotubes and bipolymers, achieving multi-layered thermal energy storage and self-healing functions.
It realizes effective anti-icing and de-icing in low-temperature environments, enhances the self-repair ability of the coating, improves thermal energy storage and ice and snow resistance, and extends the service life of the coating.
Smart Images

Figure CN119752237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating material preparation, and in particular to a double-layer composite microcapsule coating with self-repairing, high energy storage and ice and snow resistance, and a preparation method thereof. Background Art
[0002] The icing phenomenon of outdoor power transmission lines, photovoltaic equipment, transportation vehicles, etc. will not only reduce the working efficiency of the facilities and increase energy consumption, but also easily cause major accidents of life and property. Current anti-icing methods can be divided into two methods: active and passive. Active anti-icing methods include the use of mechanical devices, heating, and lowering the freezing point by spreading salt. However, these methods are often accompanied by problems such as high work intensity, low conversion efficiency, environmental pollution, and corrosion to building materials. Passive anti-icing methods, especially anti-icing coating technology, are widely used in actual engineering due to their advantages of low cost, low energy consumption, environmental protection and high application value. Coating anti-icing coatings on the surface of outdoor power transmission lines, photovoltaic equipment, transportation vehicles and other facilities is an efficient and economical anti-icing method.
[0003] Anti-icing coatings are coatings that add photothermal materials, which can effectively convert the absorbed light energy into heat, thereby significantly accelerating the melting rate of ice on the surface coating of facilities. Although these coatings show excellent deicing performance under light conditions, they are prone to lose this function under dark conditions, and the anti-icing / deicing ability of these coatings will be greatly reduced, or even completely lost in the absence of light such as cloudy days or nights, which limits their use in practical applications. Phase change materials, as a latent heat storage material with great potential, can effectively regulate the temperature of materials. To this end, researchers combined phase change materials with anti-icing / deicing coatings to achieve energy storage, storing part of the light heat in the phase change materials in the coating, and releasing the latent heat of the phase change materials at night or on rainy days, thereby achieving all-weather anti-icing and deicing performance of the coating. However, when phase change materials are directly added to the coating matrix, leakage is prone to occur, reducing the service life of the coating. In addition, microcapsules are microcontainers used to encapsulate active substances. Encapsulating phase change materials in microcapsules can prevent direct contact between the phase change materials and the matrix and avoid leakage of the phase change materials. At the same time, the microcapsule structure has high mechanical strength and thermal stability. However, although the phase change material microcapsules currently under study can store heat, they can usually only obtain heat energy by heating, and the heat energy source is single. In addition, when the surface coating materials of outdoor power transmission lines, photovoltaic equipment, transportation vehicles and other facilities are affected by strong light, ozone and other chemicals, it is easy to cause chemical damage to the low surface energy substances on the surface of the coating, causing it to lose its anti-icing performance. Summary of the invention
[0004] The present invention aims to solve the technical problems of easy leakage, single heat energy source and monotonous function of existing microcapsule phase change materials, and provides a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance, as well as its preparation method and application.
[0005] The double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance of the present invention is composed of an inner phase change microcapsule core, an inner phase change microcapsule shell, an outer self-repairing microcapsule core and an outer self-repairing microcapsule shell from the inside to the outside.
[0006] The core of the internal phase change microcapsule is a mixture of octanoic acid, tetradecane, sodium polyacrylate emulsifier and deionized water; octanoic acid and tetradecane change from liquid to solid under low temperature environment. This process releases heat, slows down the cooling rate of the coating, adjusts the low temperature environment of the coating material, and thus effectively improves the anti-icing and de-icing effect of the coating.
[0007] The inner phase change microcapsule shell is made of a mixture of carbon nanotubes, dual polymers and deionized water, wherein the dual polymers are prepared from polyvinyl alcohol and methylated hexahydroxymethyl melamine resin, and the carbon nanotubes are entangled with the dual polymers and deposited in the inner shell wall. The dual polymers as inner shell materials can improve the strength and chemical stability of the phase change microcapsules; the carbon nanotubes as photothermal materials can convert light energy into heat energy to improve the energy storage effect of the phase change material. At the same time, the carbon nanotubes generate heat energy under the action of external electric or magnetic fields to further improve the energy storage of the phase change material.
[0008] The external self-healing microcapsule core is a mixture of hydrophobic hexamethylene diisocyanate, carbon nanotubes, styrene maleic anhydride emulsifier, polyether F127 surfactant and deionized water; among them, hydrophobic hexamethylene diisocyanate is a low surface energy substance, which will gradually release and repair the damaged parts of the coating after the coating is damaged; carbon nanotubes will increase the release of hydrophobic hexamethylene diisocyanate, promote its repair of the damaged parts of the coating, and improve the self-healing effect of the coating material.
[0009] The outer self-repairing microcapsule shell is a mixture of carbon nanotubes, dual polymers and deionized water, wherein the dual polymers are prepared from polyvinyl alcohol and methylated hexamethylol melamine resin; the carbon nanotubes are entangled with the dual polymers and deposited in the outer shell wall. Among them, the dual polymer as the outer shell material can improve the responsiveness of the self-repairing microcapsule to the external environment; polyvinyl alcohol as a vulnerable part of the outer self-repairing microcapsule shell material is more susceptible to damage and can accelerate the release of the core material; methylated hexamethylol melamine resin has the advantages of high stability and harmlessness due to its high cross-linking density and low formaldehyde content; carbon nanotubes give the self-repairing microcapsule a dual mechanism of thermal induction and self-healing, enhancing the damage resistance of the shell material and the release effect of the core material.
[0010] Furthermore, in the core of the internal phase change microcapsule, the mass ratio of sodium polyacrylate emulsifier, n-octanoic acid, tetradecane and deionized water is 1:(95-100):(95-100):(190-210).
[0011] Furthermore, in the shell of the internal phase change microcapsule, the mass ratio of polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water is 1:(65-70):(1.2-1.5):(140-155).
[0012] Furthermore, in the external self-healing microcapsule core, the mass ratio of polyether F127 surfactant with a concentration of 15-20 g / L, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water is 1:(1.5-2):(2-3):(85-95):(185-200).
[0013] Furthermore, in the shell of the external self-healing microcapsule, the mass ratio of polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water is 1:(65-70):(1.2-1.5):(140-155).
[0014] The preparation method of the above-mentioned double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance is carried out according to the following steps:
[0015] 1. Preparation of internal phase change microcapsule core solution: Sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water are taken respectively in a mass ratio of 1:(95-100):(95-100):(190-210); octanoic acid and tetradecane are mixed, added into deionized water and mixed evenly, and heated until the raw materials are completely dissolved to obtain a mixed solution; the pH value of the mixed solution is adjusted to 3.5-4.5 with citric acid solution; sodium polyacrylate emulsifier is added into the mixed solution, and stirred for 20-40 minutes at a temperature of 65-75°C for emulsification to obtain a uniform and stable internal phase change microcapsule core solution;
[0016] 2. Preparation of internal phase change microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively in a mass ratio of 1: (65-70): (1.2-1.5): (140-155); polyvinyl alcohol is added to deionized water and mixed evenly, and then methyl etherified hexahydroxymethyl melamine resin is added and mixed evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 7.5-8.5 with sodium hydroxide solution, and then stirred for 20-40 minutes at a temperature of 65-75°C and a stirring speed of 500-700 r / min; finally, carbon nanotubes are added to the mixed solution, and the carbon nanotubes are entangled with the double polymer and mixed evenly through ultrasonic treatment to obtain an internal phase change microcapsule shell solution;
[0017] 3. Preparation of internal high energy storage phase change microcapsules: drip the internal phase change microcapsule shell solution into the internal phase change microcapsule core solution, and add citric acid solution to adjust the solution pH to 3.5-4.5; after dripping the internal phase change microcapsule shell solution, stir at a temperature of 65-75°C and a stirring speed of 1000-1500r / min for 60-90min to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and the carbon nanotubes and the double polymer are entangled and deposited in the inner shell wall, and the stirring is stopped after the solution temperature is naturally cooled to room temperature; then the reaction solution is filtered, washed with anhydrous ethanol, and then dried in a vacuum drying oven at a temperature of 20-30°C for 20-24h to obtain an internal high energy storage phase change microcapsule;
[0018] 4. Preparation of external self-healing microcapsule core solution: take 15-20 g / L of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water respectively according to the mass ratio of 1: (1.5-2): (2-3): (85-95): (185-200); first swell the styrene maleic anhydride emulsifier in deionized water for 20-24 hours, heat the expanded styrene maleic anhydride solution to 45-55°C, and then add sodium hydroxide solution to adjust the pH of the solution to 9.5-10.5; add hydrophobic hexamethylene diisocyanate, carbon nanotubes, and 15-20 g / L polyether F127 surfactant to the styrene maleic anhydride solution, and then stir with a high-speed shearing machine at a stirring speed of 500-700 r / min for 25-35 minutes to obtain a stable and uniform external self-healing microcapsule core solution;
[0019] 5. Preparation of external self-repairing microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively according to the mass ratio of 1: (65-70): (1.2-1.5): (140-155); polyvinyl alcohol and deionized water are stirred evenly, and added into methyl etherified hexahydroxymethyl melamine resin, stirred evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 7.5-8.5 with sodium hydroxide solution; and then stirred at a stirring speed of 500-700 r / min for 20-40 min at a temperature of 65-75°C; carbon nanotubes are then added, and after ultrasonic treatment, they are entangled with the double polymer and deposited in the outer shell wall to prepare an external microcapsule shell solution;
[0020] 6. Preparation of double-layer composite microcapsules: Add the inner high energy storage phase change microcapsules to the outer self-repairing microcapsule core solution at a temperature of 20-30°C, and then add them drop by drop to the outer self-repairing microcapsule shell solution. The outer self-repairing microcapsule core material containing the inner high energy storage phase change microcapsules attracts the outer wall material to the surrounding area through electrostatic adsorption; after the outer self-repairing microcapsule shell solution is added, the temperature is increased at a rate of 1-5°C / min. When the solution temperature rises to 65°C, citric acid solution is added to adjust the solution pH value to 4-5, and the temperature is continued to be increased at a rate of 1-5°C / min until the solution temperature reaches 80°C and stirred at this temperature at a stirring speed of 1000-1500r / min for 60-90min. The outer wall material undergoes a cross-linking and curing reaction on the surface of the core material through mechanical stirring, and the solution temperature is naturally cooled to room temperature and stirring is stopped; finally, the reaction solution is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance.
[0021] Furthermore, the ultrasonic treatment in steps 2 and 5 is performed using a cell disruptor, with an ultrasonic power of 85 to 95 W, an amplitude of 50% to 60%, and a time of 60 to 90 min.
[0022] Furthermore, in step three, the mass ratio of the internal phase change microcapsule shell solution to the internal phase change microcapsule core solution is 1:(1.4-1.6).
[0023] Furthermore, the concentration of the citric acid solution in step 1, step 3 and step 6 is 1 to 1.5 mol / L.
[0024] Furthermore, the concentration of the sodium hydroxide solution in step 2, step 4 and step 5 is 1-2 mol / L.
[0025] Furthermore, the mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution in step six is 1:(1.4-1.6).
[0026] Furthermore, the vacuum drying in step six is carried out in a vacuum drying oven at a temperature of 20 to 30° C. for 20 to 24 hours.
[0027] The application of the above-mentioned double-layer composite microcapsules with both self-repairing, high energy storage and ice and snow resistance is to use the double-layer composite microcapsules with both self-repairing, high energy storage and ice and snow resistance to prepare a coating with both self-repairing, high energy storage and ice and snow resistance; the specific method is carried out according to the following steps:
[0028] 1. Weigh 57% to 75% of E51 epoxy resin, 10% to 15% of curing agent, 5% to 8% of methacryloxypropyltrimethoxysilane as surface modifier, 3% to 5% of hydrophobic nano-silica, and 7% to 15% of double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance by mass percentage; wherein the curing agent is isophorone diamine or triethylenetetramine;
[0029] 2. Mix E51 epoxy resin, curing agent, surface modifier, hydrophobic nano-silica and double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance to obtain a mixture; then add acetone diluent, stir for 60 to 90 minutes with a mechanical stirring device at a stirring speed of 1000 to 1500 r / min; then ultrasonically treat to obtain a coating with self-repairing, high energy storage and ice and snow resistance. The coating contains double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance, which makes the coating have the characteristics of self-repairing, high energy storage and long-term ice and snow resistance.
[0030] Furthermore, the ultrasonic treatment in step 2 is performed using a cell disruptor, and the ultrasonic power is 85-95 W, the amplitude is 50%-60%, and the time is 30-40 min.
[0031] Furthermore, the added mass of the acetone diluent described in step 2 is 80% to 90% of the total mass of the mixture of E51 epoxy resin, curing agent, surface modifier, hydrophobic nano-silica and double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance.
[0032] The method for using the self-repairing, high energy storage and ice and snow resistant coating is to spray the self-repairing, high energy storage and ice and snow resistant coating on a substrate through a spray gun, and then cure it at room temperature or heat cure it at 70 to 90°C for 100 to 120 minutes to obtain a double-shell microcapsule coating with self-repairing, high energy storage and long-term ice and snow resistance.
[0033] Furthermore, the substrate is one or more of concrete, metal, asphalt, glass, fiber, plastic, wall, wire;
[0034] Furthermore, the spraying amount of the self-repairing, high energy storage and ice and snow resistant coating is 0.015-0.04 mL / cm 2 .
[0035] Compared with the prior art, the present invention breaks through the defect of the single function of traditional microcapsule composite materials and realizes the multifunctionality of microcapsules with self-repair, high energy storage and long-term anti-ice and snow. The double-layer composite microcapsules with self-repair, high energy storage and anti-ice and snow prepared by the present invention can not only repair the chemical damage suffered by the coating, but also the phase change material microcapsules have the advantages of high encapsulation rate, high light-heat conversion efficiency, high thermal conductivity, good sealing performance, good thermal stability and good mechanical properties. The heat and high energy storage generated will increase the temperature of the coating material, melt the ice and snow on the surface of the coating and inhibit the formation of ice layer, and finally realize the self-repair-high energy storage-long-term anti-ice and snow action mechanism.
[0036] The coating prepared by the double-layer composite microcapsules of the present invention with self-repairing, high energy storage and ice and snow resistance has a working process divided into two stages that are carried out in sequence, such as Figure 2 shown.
[0037] The first stage: When the coating is damaged by external forces, the shell structure of the double-layer composite microcapsule is destroyed, and the repair agent contained in the outer core is released to repair the damaged coating. At the same time, the conductive nanomaterials contained in the shell structure will generate heat energy under the action of the external electric field or magnetic field, increase the fluidity of the repair agent, and promote the self-repair effect of the damaged coating, thereby achieving the purpose of long-term durability of the coating.
[0038] The second stage: The released repair agent contains undamaged high-energy storage phase change microcapsules. After the composite microcapsule shell and outer core structure realize thermal induction and self-repair functions, the high-energy storage phase change microcapsules in the repair agent continue to play a high energy storage role. The photothermal material contained in the wall of the high-energy storage phase change microcapsule not only stores light and heat in the phase change material, but also generates heat energy under the action of external electric or magnetic fields and then stores it in the phase change material, jointly realizing comprehensive properties such as high heat storage capacity, excellent light-to-heat conversion performance and good thermal conductivity, realizing the temperature regulation function of the coating in a low-temperature environment, and effectively inhibiting the formation of ice on the coating surface.
[0039] At -20°C, the time taken for the small droplets on the surface of the coating containing 10 wt.% of the double-layer composite microcapsules of the present invention to freeze was 742 seconds, while the time taken for the small droplets on the surface of the blank coating to freeze was 56 seconds. The time taken for the small droplets on the coating containing 10 wt.% of the double-layer composite microcapsules of the present invention to freeze was about 13.3 times that of the small droplets on the blank coating. 2Under the irradiation of near-infrared lamp, the time taken for the coating droplets containing 10wt.% of the double-layer composite microcapsules of the present invention to melt is 1.9 seconds, and the time taken for the blank coating droplets to melt is 21 seconds. The time taken for the coating droplets containing 10wt.% of the double-layer composite microcapsules of the present invention to melt is about 1 / 11 of the time taken for the blank coating droplets to melt. Compared with the coating without double-layer composite microcapsules, the coating containing the double-layer composite microcapsules of the present invention has excellent anti-icing / deicing effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic structural diagram of the double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance of the present invention; in the figure, 1 is the inner phase change microcapsule core, 2 is the inner phase change microcapsule shell, 3 is the outer self-repairing microcapsule core, and 4 is the outer self-repairing microcapsule shell.
[0041] Figure 2 It is a schematic diagram of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance, which realizes two stages of self-repairing, high energy storage and ice resistance / de-icing on the surface of a substrate. DETAILED DESCRIPTION
[0042] The beneficial effects of the present invention are verified by the following examples.
[0043] Example 1: The preparation method of the double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance in this example is carried out according to the following steps:
[0044] 1. Preparation of internal phase change microcapsule core solution:
[0045] According to the mass ratio of sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water of 1:95:95:190, sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water are weighed respectively; octanoic acid and tetradecane are mixed, then added into deionized water and mixed evenly, and heated until the raw materials are completely dissolved to obtain a mixed solution; then the pH value of the mixed solution is adjusted to 4 with 1 mol / L citric acid solution; then the sodium polyacrylate emulsifier is added into the mixed solution, and stirred for 30 minutes at a temperature of 70°C for emulsification to obtain a uniform and stable internal phase change microcapsule core solution;
[0046] 2. Preparation of internal phase change microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are weighed respectively according to the mass ratio of polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water of 1:65:1.2:140; polyvinyl alcohol is added to deionized water and mixed evenly, and then methyl etherified hexahydroxymethyl melamine resin is added and mixed evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 8 with a sodium hydroxide solution having a concentration of 1.5 mol / L, and then stirred for 30 minutes at a temperature of 70°C and a stirring speed of 600 r / min; finally, carbon nanotubes are added to the mixed solution, and the carbon nanotubes are entangled with the double polymer and mixed evenly through ultrasonic treatment to obtain an internal phase change microcapsule shell solution;
[0047] 3. Preparation of internal high energy storage phase change microcapsules: according to the mass ratio of the internal phase change microcapsule shell solution to the internal phase change microcapsule core solution of 1:1.5, the internal phase change microcapsule shell solution is added dropwise to the internal phase change microcapsule core solution, and a citric acid solution with a concentration of 1 mol / L is added to adjust the solution pH value to 4; after the internal phase change microcapsule shell solution is added dropwise, the mixture is stirred at a temperature of 70°C and a stirring speed of 1500r / min for 70min to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and the carbon nanotubes and the double polymer are entangled and deposited in the inner shell wall, and the stirring is stopped after the solution temperature is naturally cooled to room temperature; the reaction solution is then filtered, washed with anhydrous ethanol, and then dried in a vacuum drying oven at a temperature of 25°C for 24h to obtain an internal high energy storage phase change microcapsule;
[0048] 4. Preparation of external self-repairing microcapsule core solution:
[0049] 15 g / L of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water were weighed in a mass ratio of 1:1.5:2:85:185. First, the styrene maleic anhydride emulsifier was swelled in deionized water for 24 hours, and the expanded styrene maleic anhydride solution was heated to 50°C, and then a 1.5 mol / L sodium hydroxide solution was added to adjust the pH of the solution to 10; hydrophobic hexamethylene diisocyanate, carbon nanotubes, and polyether F127 were added to the styrene maleic anhydride solution, and then stirred for 30 minutes with a high-speed shearing machine at a stirring speed of 700 r / min to obtain a stable and uniform external self-healing microcapsule core solution;
[0050] 5. Preparation of external self-repairing microcapsule shell solution:
[0051] According to the mass ratio of polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water of 1:65:1.2:140, polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are weighed respectively; polyvinyl alcohol and deionized water are stirred evenly, and added into methylated hexahydroxymethyl melamine resin, stirred evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 8 with a sodium hydroxide solution having a concentration of 1.5 mol / L; then stirred at a stirring speed of 600 r / min for 30 min at a temperature of 70°C; then carbon nanotubes are added, and ultrasonic treatment is performed for 30 min using a cell crusher at an ultrasonic power of 90 W and an amplitude of 50%, so that the carbon nanotubes and the double polymer are entangled and mixed evenly to obtain an external self-repairing microcapsule shell solution;
[0052] VI. Preparation of double-layer composite microcapsules
[0053] According to the mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution of 1:1.5, the internal high energy storage phase change microcapsules were added to the external self-repairing microcapsule core solution at a temperature of 25°C, and then added dropwise to the external self-repairing microcapsule shell solution. The external self-repairing microcapsule core material containing the internal high energy storage phase change microcapsules attracted the outer wall material to the surroundings through electrostatic adsorption, and the carbon nanotubes and the double polymer were entangled and deposited on the outer shell wall. After the external self-repairing microcapsule shell solution was added, the temperature was increased at a rate of 2°C / min. When the solution temperature reached 65°C, the solution was heated. 1 mol / L citric acid solution was added to adjust the pH value of the solution to 4, and the temperature was continued to be raised at a rate of 2°C / min until the solution temperature reached 80°C and stirred at this temperature at a stirring speed of 1500r / min for 60min. The outer wall material was cross-linked and cured on the surface of the core material through mechanical stirring. The solution temperature was naturally cooled to room temperature and stirring was stopped. Finally, the reaction solution was filtered, washed with anhydrous ethanol, and vacuum dried in a vacuum drying oven at a temperature of 25°C for 24 hours to obtain a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance.
[0054] Comparative Example 1: This comparative example is to prepare a single self-repairing microcapsule, and the specific steps are as follows:
[0055] 1. Preparation of self-repairing microcapsule core solution:
[0056] According to the mass ratio of 15 g / L polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water of 1:1.5:2:85:185, respectively, polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water are taken; first, the styrene maleic anhydride emulsifier is swollen in deionized water for 24 hours, the expanded styrene maleic anhydride solution is heated to 50°C, and then a sodium hydroxide solution with a concentration of 1.5 mol / L is added to adjust the pH of the solution to 10; hydrophobic hexamethylene diisocyanate, carbon nanotubes, and polyether F127 are added to the styrene maleic anhydride solution, and then stirred for 30 minutes with a high-speed shearing machine at a stirring speed of 700 r / min to obtain a stable and uniform external self-healing microcapsule core solution;
[0057] 2. Preparation of self-repairing microcapsule shell solution:
[0058] Polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively according to the mass ratio of polyvinyl alcohol, methylated hexahydroxymethyl melamine resin, carbon nanotubes and deionized water of 1:65:1.2:140; polyvinyl alcohol and deionized water are stirred evenly, and added into methylated hexahydroxymethyl melamine resin, stirred evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 8 with 1.5 mol / L sodium hydroxide solution; then stirred at a stirring speed of 600 r / min for 30 min at a temperature of 70°C; then carbon nanotubes are added, and ultrasonically treated for 70 min at an ultrasonic power of 90 W and an amplitude of 50% using a cell crusher, so that the carbon nanotubes are entangled with the double polymer and deposited in the outer shell wall to obtain a self-repairing microcapsule shell solution;
[0059] 3. Preparation of self-repairing microcapsules:
[0060] According to the mass ratio of the self-repairing microcapsule shell solution to the self-repairing microcapsule core solution of 1:1.5, the self-repairing microcapsule shell solution was added dropwise to the self-repairing microcapsule core solution. After the self-repairing microcapsule shell solution was added, the temperature was increased at a rate of 2°C / min. When the solution temperature reached 65°C, 1 mol / L citric acid solution was added to adjust the solution pH to 4. The temperature was continued to be increased at a rate of 2°C / min until the solution temperature reached 80°C and stirred at a stirring speed of 1000r / min for 60min. The outer wall material was cross-linked and cured on the surface of the core material through mechanical stirring. The solution temperature was naturally cooled to room temperature and stirring was stopped. Finally, the reaction solution was filtered, washed with anhydrous ethanol, and vacuum dried at 25°C for 24 hours to obtain a single self-repairing microcapsule.
[0061] The single self-healing microcapsule prepared in Comparative Example 1 and the double-layer composite microcapsule prepared in Example 1 were tested for their impermeability and thermal stability. After the single self-healing microcapsule and the double-layer composite microcapsule were immersed in ethanol for the same time, the mass loss rate of the core of the two microcapsules before and after immersion was tested to evaluate their impermeability.
[0062] The thermal stability of single self-healing microcapsules and double-layer composite microcapsules was analyzed by thermogravimetric analyzer at temperatures of 230-300°C, and their mass loss rate was used as an evaluation indicator.
[0063] The exothermic enthalpy of single phase change microcapsules and double-layer composite microcapsules was tested by differential scanning calorimetry.
[0064] The yield stress of single phase change microcapsules and double-layer composite microcapsules was tested by nanoindentation tester. In the nanoindentation test, the force was set to 50nN, maintained for 10s, and the displacement resolution was 0.01nm. The yield stress values of single phase change microcapsules and double-layer composite microcapsules at pH 5.0 were calculated based on the obtained load-displacement curves.
[0065] The test results are listed in Table 1.
[0066] Table 1 Performance comparison of the single phase change microcapsule of comparative example 1 and the double-layer composite microcapsule of embodiment 1
[0067]
[0068] Compared with single self-repairing microcapsules, double-layer composite microcapsules have stronger impermeability and thermal stability, indicating that they are more stable and more conducive to the realization of microcapsule self-repairing function. Compared with single phase change microcapsules, double-layer composite microcapsules have greater yield stress and greater exothermic enthalpy value, indicating that double-layer composite microcapsules have better mechanical properties and can better adjust the low temperature environment of coating materials and alleviate the ice phenomenon on the surface of coating materials.
[0069] The double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance prepared in Example 1 are used to prepare a coating with self-repairing, high energy storage and ice and snow resistance; the specific method is carried out according to the following steps:
[0070] 1. Weigh 63 grams of E51 epoxy resin, 15 grams of curing agent triethylenetetramine, 8 grams of methacryloxypropyltrimethoxysilane as a surface modifier, 4 grams of hydrophobic nano-silica, and 10 grams of double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance;
[0071] 2. E51 epoxy resin, triethylenetetramine, methacryloxypropyltrimethoxysilane, hydrophobic nano-silica and double-layer composite microcapsules with self-repairing, high energy storage and anti-ice and snow properties were mixed to obtain a mixture; 110 mL of acetone diluent (density 0.79 g / cm 3 ), stirred for 80 minutes at a stirring speed of 1000 r / min using a mechanical stirring device; then subjected to ultrasonic treatment for 30 minutes using a cell crusher at an ultrasonic power of 90 W and an amplitude of 50% to obtain a coating with self-repairing, high energy storage and ice and snow resistance.
[0072] At the same time, the double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance were not added to prepare the comparative coating.
[0073] The self-repairing, high energy storage and ice and snow resistance coating and the comparative coating were sprayed on the same substrate, which was a plexiglass plate (area 100cm 2 ), droplet freezing and deicing tests were carried out on the two coatings.
[0074] The droplet freezing test was performed by placing the two coatings in an environmental chamber at a temperature of -20°C and a relative humidity of 30%; then placing a small droplet of 5 μl on the surface of each of the two coatings.
[0075] The deicing test was conducted by placing the two coatings in an environmental chamber at -5°C and 85% relative humidity. An air humidifier was placed in the environmental chamber to induce the formation of water droplets on the coating surface. Subsequently, the air humidifier was turned off and the coating was exposed to near infrared (200 mW / cm 2 ) and observed the melting time of water droplets on the surfaces of the two coatings.
[0076] The test results of the two coatings are as follows:
[0077] At -20°C, it takes 742 seconds for small droplets on the surface of the coating containing 10wt.% of double-layer composite microcapsules to freeze, while it takes 56 seconds for small droplets on the surface of the blank coating to freeze. The time taken for small droplets on the coating containing 10wt.% of double-layer composite microcapsules to freeze is approximately 13.3 times that of the blank coating.
[0078] At 200mW / cm 2 Under the irradiation of near-infrared lamp, it takes 1.9 seconds for small droplets of double-layer composite microcapsule coating containing 10wt.% to melt, while it takes 21 seconds for small droplets of blank coating to melt. The time taken for small droplets of double-layer composite microcapsule coating containing 10wt.% to melt is about 1 / 11 of the time taken for small droplets of blank coating to melt.
[0079] In summary, the coating containing double-layer composite microcapsules has excellent anti-icing / de-icing effect compared with the coating without double-layer composite microcapsules.
Claims
1. A double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance, which is composed of an inner phase change microcapsule core, an inner phase change microcapsule shell, an outer self-repairing microcapsule core and an outer self-repairing microcapsule shell from the inside to the outside; The internal phase change microcapsule core is a mixture of octanoic acid, tetradecane, sodium polyacrylate emulsifier and deionized water; the internal phase change microcapsule shell is a mixture of carbon nanotubes, a double polymer and deionized water, wherein the double polymer is prepared from polyvinyl alcohol and methyl etherified hexamethylol melamine resin; The external self-healing microcapsule core is mixed with hydrophobic hexamethylene diisocyanate, carbon nanotubes, styrene maleic anhydride emulsifier, polyether F127 surfactant and deionized water; the external self-healing microcapsule shell is mixed with carbon nanotubes, a double polymer and deionized water, wherein the double polymer is prepared from polyvinyl alcohol and methylated hexahydroxymethylmelamine resin.
2. A method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance as claimed in claim 1, characterized in that: The method proceeds as follows:
1. Preparation of internal phase change microcapsule core solution: Sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water are taken respectively in a mass ratio of 1:(95-100):(95-100):(190-210); octanoic acid and tetradecane are mixed, added into deionized water and mixed evenly, and heated until the raw materials are completely dissolved to obtain a mixed solution; the pH value of the mixed solution is adjusted to 3.5-4.5 with citric acid solution; sodium polyacrylate emulsifier is added into the mixed solution, and stirred for 20-40 minutes at a temperature of 65-75°C for emulsification to obtain a uniform and stable internal phase change microcapsule core solution; 2. Preparation of internal phase change microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively in a mass ratio of 1: (65-70): (1.2-1.5): (140-155); polyvinyl alcohol is added to deionized water and mixed evenly, and then methyl etherified hexahydroxymethyl melamine resin is added and mixed evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 7.5-8.5 with sodium hydroxide solution, and then stirred for 20-40 minutes at a temperature of 65-75°C and a stirring speed of 500-700 r / min; finally, carbon nanotubes are added to the mixed solution, and the carbon nanotubes are entangled with the double polymer and mixed evenly through ultrasonic treatment to obtain an internal phase change microcapsule shell solution; 3. Preparation of internal high energy storage phase change microcapsules: drip the internal phase change microcapsule shell solution into the internal phase change microcapsule core solution, and add citric acid solution to adjust the solution pH to 3.5-4.5; after dripping the internal phase change microcapsule shell solution, stir at a temperature of 65-75°C and a stirring speed of 1000-1500r / min for 60-90min to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and the carbon nanotubes and the double polymer are entangled and deposited in the inner shell wall, and the stirring is stopped after the solution temperature is naturally cooled to room temperature; then the reaction solution is filtered, washed with anhydrous ethanol, and then dried in a vacuum drying oven at a temperature of 20-30°C for 20-24h to obtain an internal high energy storage phase change microcapsule; 4. Preparation of external self-healing microcapsule core solution: take polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, hydrophobic hexamethylene diisocyanate and deionized water at a concentration of 15-20 g / L respectively according to the mass ratio of 1: (1.5-2): (2-3): (85-95): (185-200); first swell the styrene maleic anhydride emulsifier in deionized water for 20-24 hours, heat the expanded styrene maleic anhydride solution to 45-55 ° C, and then add sodium hydroxide solution to adjust the pH of the solution to 9.5-10.5; add hydrophobic hexamethylene diisocyanate, carbon nanotubes, and polyether F127 surfactant to the styrene maleic anhydride solution, and then stir with a high-speed shearing machine at a stirring speed of 500-700 r / min for 25-35 minutes to obtain a stable and uniform external self-healing microcapsule core solution; 5. Preparation of external self-repairing microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively according to the mass ratio of 1: (65-70): (1.2-1.5): (140-155); polyvinyl alcohol and deionized water are stirred evenly, and added into methyl etherified hexahydroxymethyl melamine resin, stirred evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 7.5-8.5 with sodium hydroxide solution; and then stirred at a stirring speed of 500-700 r / min for 20-40 min at a temperature of 65-75°C; carbon nanotubes are then added, and after ultrasonic treatment, they are entangled with the double polymer and deposited in the outer shell wall to prepare an external microcapsule shell solution; 6. Preparation of double-layer composite microcapsules: Add the inner high energy storage phase change microcapsules to the outer self-repairing microcapsule core solution at a temperature of 20-30°C, and then add them dropwise to the outer self-repairing microcapsule shell solution. The outer self-repairing microcapsule core material containing the inner high energy storage phase change microcapsules attracts the outer wall material to the surrounding through electrostatic adsorption; After the external self-repairing microcapsule shell solution is added, the temperature is increased at a rate of 1 to 5°C / min. When the solution temperature reaches 65°C, citric acid is added to adjust the solution pH value to 4 to 5. The temperature is continued to be increased at a rate of 1 to 5°C / min until the solution temperature reaches 80°C and stirred at this temperature at a stirring speed of 1000 to 1500 r / min for 60 to 90 minutes. The outer wall material undergoes a cross-linking and curing reaction on the surface of the core material through mechanical stirring. The solution temperature is naturally cooled to room temperature and stirring is stopped. Finally, the reaction solution is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance.
3. The method of preparing a double-layer composite microcapsule having self-repairing, high energy storage and ice and snow resistance according to claim 2, characterized in that: The ultrasonic treatment described in steps 2 and 5 is performed using a cell crusher, with an ultrasonic power of 85 to 95 W, an amplitude of 50% to 60%, and a time of 60 to 90 min.
4. The method of preparing a double-layer composite microcapsule having self-repairing, high energy storage and ice and snow resistance according to claim 2 or 3, characterized in that: In step three, the mass ratio of the internal phase change microcapsule shell solution to the internal phase change microcapsule core solution is 1:(1.4-1.6).
5. The method of preparing a double-layer composite microcapsule having self-repairing, high energy storage and ice and snow resistance according to claim 2 or 3, characterized in that: The concentration of the citric acid solution in step 1, step 3 and step 6 is 1-1.5 mol / L.
6. The method of preparing a double-layer composite microcapsule having self-repairing, high energy storage and ice and snow resistance according to claim 2 or 3, characterized in that: The concentration of the sodium hydroxide solution in step 2, step 4 and step 5 is 1-2 mol / L.
7. The method of preparing a double-layer composite microcapsule having self-repairing, high energy storage and ice and snow resistance according to claim 2 or 3, characterized in that: The mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution described in step six is 1:(1.4-1.6).
8. The use of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance as claimed in claim 1, characterized in that: This application is to use double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance to prepare a coating with self-repairing, high energy storage and ice and snow resistance.
9. The use of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance according to claim 8, characterized in that: The specific method for preparing a coating having both self-repairing, high energy storage and anti-ice and snow by using a double-layer composite microcapsule having both self-repairing, high energy storage and anti-ice and snow is carried out in the following steps:
1. Weigh 57% to 75% of E51 epoxy resin, 10% to 15% of curing agent, 5% to 8% of methacryloxypropyltrimethoxysilane as surface modifier, 3% to 5% of hydrophobic nano-silica, and 7% to 15% of double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance by mass percentage; wherein the curing agent is isophorone diamine or triethylenetetramine; 2. Mix E51 epoxy resin, curing agent, surface modifier, hydrophobic nano-silica and double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance to obtain a mixture; then add acetone diluent, and stir with a mechanical stirring device at a stirring speed of 1000-1500r / min for 60-90min; then ultrasonically treat to obtain a coating with self-repairing, high energy storage and ice and snow resistance.
10. The use of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance according to claim 9, characterized in that: The added mass of the acetone diluent described in step 2 is 80% to 90% of the total mass of the mixture of E51 epoxy resin, curing agent, surface modifier, hydrophobic nano-silica and double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance.
Citation Information
Patent Citations
Self-healing microcapsule and preparation method thereof, paint, coating and epoxy resin composite material
CN107159070A
Method for preparing organic / inorganic composite double-layer wall material high-thermal resistance microcapsule for selfreparing of pitch
CN107400373A
Double-shell epoxy resin microcapsule self-repair material and preparation method thereof
CN108892407A
Asphalt material based on phase change capsule and preparation process thereof
CN113861704A
Preparation method of self-temperature-adjusting asphalt pavement change microcapsule in large-temperature-difference region
CN115322752A
Cited By
High-wear-resistance self-repairing composite floor coating and preparation process thereof
CN120399543A
Self-repairing material applied to phase change temperature control and preparation method thereof
CN122147695A